Financial Liberalizations in Latin-America in the 1990s: A Reassessment - Joshua Aizenman (University of California, Economics Department, 2005)
This paper studies the experience of Latin-America [LATAM] with financial liberalization in the 1990s. The rush towards financial liberalizations in the early 1990s was associated with expectations that external financing would alleviate the scarcity of saving in LATAM, thereby increasing investment and growth. Yet, the data and several case studies suggest that the gains from external financing are overrated. The bottleneck inhibiting economic growth is less the scarcity of saving, and more the scarcity of good governance. A possible interpretation for these findings is that in countries where private savings and investments were taxed in an arbitrary and unpredictable way, the credibility of a new regime could not be assumed or imposed. Instead, credibility must be acquired as an outcome of a learning process. Consequently, increasing the saving and investment rates tends to be a time consuming process. This also suggests that greater political instability and polarization would induce consumers to be more cautious in increasing their saving and investment rates following a reform. Hence, reaching a sustained take-off in Latin-America is a harder task to accomplish than in Asia.
Keywords: 330; Financial liberalization; External financing; Self-financing